Teachers’ Insights: : Exploring In-Service Teacher Education in Select Districts of Punjab - Garg, Bharati; Gupta, Bhawna (Voices of Teachers and Teacher Educators, 2024)
Teachers form the backbone of the education system, and their continuous professional development is crucial for improving student outcomes. The Government of India (GoI) has placed significant emphasis on enhancing teachers’ capacity to deliver and improve learning outcomes, apart from focusing on other parameters for imparting quality education. The government of Punjab has taken proactive steps to improve professional development opportunities for teachers. This study examines the state government’s perception of government middle school teachers from two districts—SAS Nagar and Ferozepur— regarding the quality and effectiveness of in-service training imparted to teachers by the State Council of Educational Research and Training (SCERT), Punjab. The findings provide valuable insights into the effectiveness, relevance and impact of SCERT’s initiatives. Additionally, the research identifies the challenges faced by teachers and head teachers in implementing these training programs and provides policy recommendations to enhance the overall quality of teacher education in the State. While the Punjab government has taken commendable steps to enhance teacher development, addressing challenges related to quality and accountability is essential to maximise the impact of these training programs.